2007
DOI: 10.2202/1556-3758.1112
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Physiochemical Properties of Banana Paste under Vacuum Dehydration

Abstract: This research aimed to develop a prototype of an evaporative dehydrator and demonstrate the effect of quick evaporative dehydration on the physiochemical properties of banana paste. The study was divided into 2 parts. The first part was focused on the development of the evaporative dehydrator prototype. After several modifications, the prototype of an evaporative dehydrator was successfully constructed to enable the variation of banana paste sample prior to evaporation using two types of evaporative stresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It was found by monitoring the samples in the present study that the flour obtained from peach peel had a darker colour than that produced from pulp. Because of the possible existence of some browning contributor enzymes, such as polyphenol oxidase, and the occurrence of the Maillard reaction (31), a significant colour change was observed during the peel drying process in the present study, from which dark brown powder was produced from the peel. The L* , a* , and b* values were found to be 76, 5.5, and 29.39 in peach pulp flour, and 56, 12.2, and 34 in peach peel flour, respectively (7), and these results are in agreement with the results of the present study.…”
Section: Resultsmentioning
confidence: 72%
“…It was found by monitoring the samples in the present study that the flour obtained from peach peel had a darker colour than that produced from pulp. Because of the possible existence of some browning contributor enzymes, such as polyphenol oxidase, and the occurrence of the Maillard reaction (31), a significant colour change was observed during the peel drying process in the present study, from which dark brown powder was produced from the peel. The L* , a* , and b* values were found to be 76, 5.5, and 29.39 in peach pulp flour, and 56, 12.2, and 34 in peach peel flour, respectively (7), and these results are in agreement with the results of the present study.…”
Section: Resultsmentioning
confidence: 72%
“…Major change in colour took place during drying of the peel that yielded dark brown powder, particularly in the ripe samples. As banana peel contains glucose, fructose and protein (Emaga et al, 2007), an extend of the Maillard reaction could had occurred, while certain enzymes such as polyphenol oxidase may be present in banana peel that could contribute a certain degree of enzymatic browning (Thipayarat, 2007). This later explanation seems acceptable since the enzymatic browning of banana is well known problem.…”
Section: General Descriptive Statisticsmentioning
confidence: 99%
“…Inconsistency in b ⁄ value might have been attributed to the excessive browning occurring in the peel during drying, and to some extend the presence of dark spots scattering about the flour and interfere with colour analyses. No study could be found on the effect of drying on banana peel, but quality of banana paste as influenced by vacuum dehydration has been studied by Thipayarat (2007). It was found that banana paste dehydrated with vacuum dehydration had darker colour (lower L value) and more intense yellow colour (higher b value) that was hypothesised to be due to condensation and to moisture loss, enzymatic and non-enzymatic browning (Thipayarat, 2007).…”
Section: General Descriptive Statisticsmentioning
confidence: 99%
“…This comparative color advantage is remarkable, given that the HCh had a high content of soluble solids and was dehydrated at 50 °C, while that obtained by (Alkarkhi, Bin Ramli, Yong, & Easa, 2011) had a lower content of soluble solids and was dehydrated at 60 °C. Therefore, it is likely that the use of antioxidant has not been effective, favoring the Maillard reaction and the high enzymatic activity of the polyphenol oxidase present in the banana that could contribute to a certain degree of enzymatic browning (Thipayarat, 2007). Enzymatic browning of bananas is a well-known problem, although also in cherimoya, the use of sodium bisulfite as an antioxidant result being effective for this type of Annona.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%